(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The microstructure and properties of spheroidal graphite cast irons and austempered ductile irons with nanosized additives of titanium carbonitride and titanium nitride (TiCN+TiN), titanium nitride TiN and cubic boron nitride cBN are investigated. The microstructure of the patterns is observed by optical metallography, quantity metallographic analysis, X-Ray analysis, SEM analysis and EDX analysis. Hardness measurement, impact strength and abrasion wear test on fixed abrasive are performed. The influence of the nanosized additives on the microstructure, mechanical and tribological properties of the cast irons are examined.